THE CONCEPT OF “WEALTH” IN ENGLISH AND UZBEK LINGUOCULTURAL TRADITIONS A STUDY BASED ON PHRASEOLOGICAL UNITS, PROVERBS, AND SAYINGS - Ismonova Minavvar Salohiddin qizi (SPAIN- SCIENTIFIC REVIEW OF THE PROBLEMS AND PROSPECTS OF MODERN SCIENCE AND EDUCATION, 2025)
This article examines the representation of the concept of “wealth” in English and Uzbek through phraseological units, proverbs, and sayings within a linguocultural framework. The formation of this concept in both languages is shown to be closely connected with each nation’s historical experience, economic practices, moral–ethical principles, and cultural values, all of which are reflected in the semantic structure of their respective phraseological systems. The analysis reveals that, in English, wealth is predominantly interpreted through pragmatic, economic, and individually oriented criteria, whereas in Uzbek, it is closely associated with such moral and spiritual categories as baraka (divine abundance), rizq (sustenance), honesty, and generosity. During the study, the imagery, evaluative components, conceptual fields, and cultural meanings embedded in the phraseological units of both languages were compared, demonstrating how each community constructs and conceptualizes the notion of wealth through linguistic expression. The findings indicate that an econometric and functional interpretation of wealth is dominant in English phraseology, while in Uzbek, ethical and spiritual dimensions prevail within the conceptualization of this notion.